MEMBANGUN KARAKTER SISWA DALAM PEMBELAJARAN BIOLOGI - Lepiyanto, Agil (Bioedukasi Jurnal Pendidikan Biologi, 2011)
Character is the way ot thinking and behaving every person in their living, such as in the family, community, and nation. Person who have good character are individuals who can make decisions, consistant, and consequence with their attitude and behavior. The reasons show that a character education needs to be invested as early as possible anticipate all of future problem. In biology learning, students can train responsibility value, care to environtment and conservation effort. Based on the rasional, teachers should be facilitate the students character building through the planning and implementation character education based biology learning.Â Kata Kunci: Karakter Siswa, Pembelajaran Biologi